Towards 'good enough' climate and disaster risk governance: Emerging lessons from Zambia, Nepal, Viet Nam and Uganda - Ian Christoplos; Charles Aben; Bernard Bashaasha; Hari Dhungana; Esbern Friis-Hansen; Mikkel Funder; Nguyen Thi Thanh Huong; Dil Bahadur Khatri; Lily Lindegaard; Carol Mweemba; Le Duc Ngoan; Imasiku Nyambe; et al. (Danish Institute for International Studies (DIIS), 2014)
This report compares and contrasts how disaster risk management is being conceptualised in relation to emerging climate change adaptation efforts and how these two agendas are influenced by different governance systems, accountabilities and social contracts in Zambia, Uganda, Viet Nam and Nepal. Particular attention is paid to how this relates to different forms of state legitimacy and the changing role of local government in connection with a range of decentralisation processes, increasing political attention and the lure of new but little understood climate change funding. Findings highlight how concerns about disaster risk are influencing how new and uncertain forms of combined disaster/climate governance are perceived and implemented. Increasing attention from the media is also noted as a key factor determining which aspects of disaster risk management gain prominence, and which are ignored in public demands and in responses by politicians and local government.
Keywords: 300; Climate change and environment; Development policies and practice; Food and agriculture; Zambia; Nepal; Vietnam; Uganda